2015
DOI: 10.5656/ksae.2015.06.0.016
|View full text |Cite
|
Sign up to set email alerts
|

Damage, Occurrence, and Optimal Control Period of Eurytoma maslovskii Affecting Japanese Apricot (Prunus mume) Fruits in Jeonnam Province

Abstract: Fruit drop due to Eurytoma maslovskii infestations of Japanese apricot (Prunus mume) is a serious economic issue in most parts of Jeonnam Province, with the exception of the coastal areas such as Wando, Shinan, Yeosu, and Muan. The average incidence of fruit drop was 67% in 2013 and 33.3% in 2014. E. maslovskii larvae overwinter inside the pits of Japanese apricots. Larval survival rates decrease to less than 30% after a rainy summer season. The eggs are long oval of 0.68 mm, 0.29 mm and ivory white. Mature la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…ansu Max., and peach Prunus persica (L.) Batsch [ 3 ]. Since its first occurrence in 1979 [ 4 ], E. maslovskii has become a destructive pest in the main apricot production area in Korea [ 3 , 5 ]. In China, the occurrence of E. maslovskii has been confirmed in Hebei [ 6 ], Liaoning, Chaoyang [ 2 ], Zhejiang [ 7 ], and Shandong [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…ansu Max., and peach Prunus persica (L.) Batsch [ 3 ]. Since its first occurrence in 1979 [ 4 ], E. maslovskii has become a destructive pest in the main apricot production area in Korea [ 3 , 5 ]. In China, the occurrence of E. maslovskii has been confirmed in Hebei [ 6 ], Liaoning, Chaoyang [ 2 ], Zhejiang [ 7 ], and Shandong [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In China, the occurrence of E. maslovskii has been confirmed in Hebei [ 6 ], Liaoning, Chaoyang [ 2 ], Zhejiang [ 7 ], and Shandong [ 8 ]. The fruits infested by E. maslovskii result in the non-development of the flesh leading to a loss of apricot fruit production of 33.3–67% [ 5 ], and up to 80% of the crop being severely infested [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, organic farms' Japanese apricot fruit damage rate caused by Eurytoma maslovskii was measured to be 36.7% in 2017 and 23.3% in 2018, both of which were significantly higher than conventional farms' fruit damage rate. Choi et al [40] reported that the overall Japanese apricot fruit damage rate caused by Eurytoma maslovskii was 67.3% in 2013 and 33.3% in 2014 in Jeonnam Province. It soared to 90% in one of the most serious cases in the past [41].…”
Section: Soil Chemical Properties and Yield Of Japanese Apricotmentioning
confidence: 99%